2009
DOI: 10.1140/epje/i2009-10509-4
|View full text |Cite
|
Sign up to set email alerts
|

Single flexible and semiflexible polymers at high shear: Non-monotonic and non-universal stretching response

Abstract: Using Brownian hydrodynamic simulation techniques, we study single polymers in shear. We investigate the effects of hydrodynamic interactions, excluded volume, chain extensibility, chain length and semiflexibility. The well-known stretching behavior with increasing shear rate [Formula: see text] is only observed for low shear [Formula: see text] < [Formula: see text] , where [Formula: see text] is the shear rate at maximum polymer extension. For intermediate shear rates [Formula: see text] < [Formula: see text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 27 publications
14
43
0
Order By: Relevance
“…1b. The transition between isotropic and prolate conformations (orange line) extends into the coil state and separates the slipping isotropic coil state SC from the slipping prolate coil state SPC, in agreement with previous observations [13,33]. In fig.…”
Section: Fixed Shear Rate Variable Cohesive Strengthsupporting
confidence: 91%
“…1b. The transition between isotropic and prolate conformations (orange line) extends into the coil state and separates the slipping isotropic coil state SC from the slipping prolate coil state SPC, in agreement with previous observations [13,33]. In fig.…”
Section: Fixed Shear Rate Variable Cohesive Strengthsupporting
confidence: 91%
“…63 It also indicates that decrease in polymer size observed in this article is not related to ultra-high shear rate (Wi > N 2 K ) compaction of the polymer chain studied by Sendner and Netz, 67 and later elucidated by Dalal et al 66 Further evidence pointing to attachment of colloids in stretched polymers leading to globule formation by the mechanism described above is that the MFPT is inversely proportional to colloid concentration as shown in the supplementary material. 63 The breakup of globules in shear flow has received much attention recently due to its importance in biology and in determining properties of gels.…”
Section: B Impact Of Shear Flow On Globule Formation and Breakupsupporting
confidence: 60%
“…1,2 The influence of EV on the behaviors of polymer chains in shear flow is a subject of great interest including the fundamental understanding of solvent quality, 1 and novel technological applications for polymer separation and purification. [14][15][16][17][18][19][20][21] Experimentally, Muller et al observed that linear polymers have larger stretching and weaker orientation in good solvents than in theta solvents based on a light scattering study of in situ flow. [14][15][16][17][18][19][20][21] Experimentally, Muller et al observed that linear polymers have larger stretching and weaker orientation in good solvents than in theta solvents based on a light scattering study of in situ flow.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The HI makes buried or exposed polymer monomers feel different solvent drag. 17,19,[31][32][33] Sendner and Netz found that the dominant HI, which screens interior monomers from hydrodynamic drag, can reduce the stretching of linear chains under shear. In the fully extended conformation, more monomers are exposed to the flow, and the effects of HI are diminished.…”
Section: Introductionmentioning
confidence: 99%